Effect of Naphthyridine-Like Structure in Polyacrylonitrile Stabilized Fibers on the Modulus of Carbon Fibers - Zhao, Chun; Gao, Aijun; Wang, Kai; Kong, Lingqiang; Xu, Lianghua (Asian Journal of Chemistry, 2013)
Correlation between naphthyridine-like structures of polyacrylonitrile stabilized fibers and modulus of carbon fibers was investigated. It was found that naphthyridine-like structures, which is a kind of characteristics structure in the polyacrylonitrile stabilized fibers, influence the modulus of carbon fibers. The naphthyriding-like structures can convert to graphite layers, which induce the degree of graphitization and crystallite size to improve, so the more the naphthyriding-like structures form in the polyacrylonitrile stabilized fibers, the higher the modulus of carbon fibers is.